Uganda christian university - SWABALE NOUR LEILAH (Uganda christian university, 2024)
This dissertation examines the impact of staff training on customer satisfaction in terms of the quality and consistency of food and beverage service. The study has been set against the backgrounds of selected hotels in Kampala, Uganda. Nowadays, the hospitality industry increasingly realizes that attentive standards of service are an indispensable differential element of its business undertaking, and this research will explore quantitatively how such specific training can affect customer perceptions and their levels of gratification.This qualitative-quantitative research, based on the case study approach, determines the effectiveness of training programs. It further ascertains, through survey and interview, hotel employees and guests to analyze changes in training programs affecting the services provided and the overall customer experience. Metrics include not just the quality of the service but consistency also, with implications for customer satisfaction.The results clearly indicate that thorough training of the staff is positively correlated with an increase in customer satisfaction. Indeed, the hotels that had systematic training programs showed a better quality of service and consistency, thus leading to a higher degree of satisfaction among guests. This study emphasizes the importance of continuous development of staff for maintaining high standards within the highly competitive food and beverage industry.The knowledge base this research adds to hospitality management studies is garnished with actionable recommendations that might be implemented by hotel management teams. This paper identifies the importance of continuous training among staff in the course of helping hotels in Kampala and settings with similar conditions raise the service provision bar in order to increase customer satisfaction.